A global law of diversity : evolving models and concepts - Alessi, Nicolò Paolo (Routledge advances in minority studies, 2025)
"This book provides a global perspective on the accommodation of diversity within constitutional traditions, considering the most innovative approaches and legal instruments of the Global North and Global South. This field of study, traditionally dominated by a Global North approach based on majority-minority and rights-based discourse, is undergoing significant development. The work thus assesses the appropriateness of the existing mainstream theoretical tools and concepts - in particular minority and minority-related concepts as well as rights discourse - to grasp the ongoing evolution of this field of law. A reconsideration of the traditional conceptual categories and the introduction of the concept "Law of Diversity" is proposed as a theoretical framework to grasp the ongoing developments in this area. Among the models studied, those that are referred to as emergent models for the accommodation of diversity in the Global North appear to be particularly in need of theoretical recognition. To this end, the theory of federalism is used to serve a rather unexplored theoretical function. Federal theory is put forward as a theoretical instrument to frame and explain the emergent instruments for the accommodation of diversity, as well as provide practical solutions for their development. The book will be of interest to researchers, academics and policy-makers working in the areas of comparative constitutional law, minority and indigenous rights law, and federal studies"--